Mortality of breast cancer in Taiwan, 1971-2010: Temporal changes and an age-period-cohort analysis - M.-L. Ho; Y.-H. Hsiao; S.-Y. Su; M.-C. Chou; Y.-P. Liaw (Taylor & Francis Group, 2015)
AbstractThe current paper describes the age, period and cohort effects on breast cancer mortality in Taiwan. Female breast cancer mortality data were collected from the Taiwan death registries for 1971-2010. The annual percentage changes, age- standardised mortality rates (ASMR) and age-period-cohort model were calculated. The mortality rates increased with advancing age groups when fixing the period. The percentage change in the breast cancer mortality rate increased from 54.79% at aged 20-44 years, to 149.78% in those aged 45-64 years (between 1971-75 and 2006-10). The mortality rates in the 45-64 age group increased steadily from 1971 to 1975 and 2006-10. The 1951 birth cohorts (actual birth cohort; 1947-55) showed peak mortalities in both the 50-54 and 45-49 age groups. We found that the 1951 birth cohorts had the greatest mortality risk from breast cancer. This might be attributed to the DDT that was used in large amounts to prevent deaths from malaria in Taiwan. However, future researches require DDT data to evaluate the association between breast cancer and DDT use.